Sistem Informasi Pemesanan Tiket Berbasis Web Pada PO. Lapan-Lapan Travel Kota Jambi - Agung Kurniawan, Ade; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2023)
Technological advances that continue to grow always provide new changes in improving the quality and performance of a company. Related to the operational activities of the PO ticket booking business. Eight-Lapan Travel Kota Jambi currently that customers must come to the outlet to make ticket reservations and travel operator officers often experience errors in terms of giving seat numbers or recording the desired departure hours by prospective customers. As well as the obstacles in managing advice information from consumers due to the process of information advice and complaints using via sms. The author of web-based information system design using protoype methods includes diagaram use cases, activity diagrams, display design diagram classes, database structure tables. The result of this study is to analyze and build an information system design that can help automate the ticket booking process. The design of the system built can help to be a reference for travel parties related to the obstacles faced regarding the current business process of ticket booking operations.